ANALYSIS OF THE IMPACT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. TELKOM AKSES MEDAN - Siregar, Amelia Padillah; Aslami, Nuri (Transpublika Publisher, 2022)
Employee performance is the process of attaining the company's organizational goals in accordance with the company's regulations. To achieve optimal work results, the organization must have disciplined personnel, as discipline is an attitude that demonstrates the employee's commitment to the job. Therefore, to produce disciplined employees, it is necessary to provide these employees with direction and desire to work harder, which will result in the production of high-quality goods and skilled personnel. This study aims to analyze the impact of work motivation and work discipline on employee performance at PT. Telkom Akses Medan. This study employs a quantitative methodology with an associative approach. The population consists of all PT Telkom Akses Medan personnel, and the sample size is 79 individuals. The results indicate that despite the fact that PT Telkom Akses Medan employees lack discipline, work discipline has no effect on employee performance, since the performance is very fulfilling and the company appreciates the way it operates. This study also demonstrates that PT Telkom Akses Medan's performance is significantly affected by employee motivation.